Ear Infection and Its Associated Risk Factors, Comorbidity, and Health Service Use in Australian Children - Vasoontara Yiengprugsawan; Anthony Hogan (Hindawi Limited, 2013)
This study investigates and identifies risk factors, comorbidity, and health service use related to ear infection in Australian children. Two cross-sectional analyses of the Longitudinal Study of Australian Children (LSAC) involved 4,983 children aged 4 to 5 years in 2004 and aged 10 to 11 years in 2010. Odds ratios (ORs) were analysed using bivariate logistic regression. The prevalence of parent-reported ear infection was 7.9% (394) among children aged 4 to 5 years and 3.3% (139) at 10 to 11 years. Our study found that risk factors associated with ear infection were indigenous status, not being breastfed, mother or father smoking at least once a day, and father's school completion at year 9 or lower. By age 10 to 11 years significantly reported comorbidities were tonsillitis (OR 4.67; P<0.001), headache (OR 2.13; P=0.006), and asthma (OR 1.67; P=0.003) and ear infection was found to be associated with the use of pediatrician (OR 1.83; P=0.031), other specialist (OR 2.12; P<0.001), and early intervention services (OR 3.08; P=0.010). This empirical evidence can be used to inform the development of intervention and management programs for ear infection.